Democracy And Resurgence of Coups in Africa: The Implications For The African Union - Onome Odokuma (Universitas Muhammadiyah Ponorogo, 2026)
This study explored democracy and resurgence of coups in Africa: the implications for the African Union. The major focus is on reasons why there is a sudden reoccurrence of military coups in Africa and what spurs their successes and/or failures so far in the region. Using the secondary data collection method, the study identified the major causes of occurring coups in Africa and also using the regime security theory, the reasons for the spiraling effect of military coups in Nigeria was found to be similar in most of the countries that recently engaged in coups and countercoups. Furthermore, the theory provided for mostly the successes in these countries and why they would always succeed. The study went further to account for the efforts made by the African Union and other economic organizations in the region to reduce the spread of coups in Africa. The study concludes that the African Union and other related economic organizations also end up having some form of political and economic interests in remaining in power for their own selfish gains hence the cycle of resurgence of military coups in Africa. Key words: Democracy, resurgence, coup, African Union